Atención al cliente y su incidencia en la percepción de los usuarios de las compañías de taxis del cantón Valencia. - Ramos Jiménez, Odalis Leidy (2022)
The present work entitled "Customer service and its impact on the perception of users of taxi companies in the Canton of Valencia". The research was carried out in order to analyze the incidence of customer service and the perception of users of the taxi companies of Canton Valencia, for the knowledge of the various factors that affect its functioning, seeking to generate strategies to meet the expectations of the user. The bibliographic research tries to compile the necessary information of the variables of study by means of the search of books, scientific magazines, and web pages, as well as the field research where it was applied because of compiling the data that the surveys yield. The direct beneficiaries were the users of the companies, who at the moment of acquiring the taxi service are directly linked to the company. The sample consisted of 52 partners and 157 clients of the service. The results show that the majority of clients are satisfied with the service provided, however, they should improve the attention, the prices are considered a little high for the quality of the service provided, likewise, it is denoted that there is no training by the taxi company, so the authors recommend the development of a training plan related to customer service issues in order to improve the quality of service.